The ABCs of 4-H: A Primer for 4-H Volunteers - Keith G. Diem; Sarah Hensley; Ben Knowles (EDIS)
This information sheet is the introduction to the 4-H Volunteer Training Series (VTS). The series contains a wealth of information, from how to start a club, to planning field trips, to how to work with youth. This 5-page fact sheet was written by Keith G. Diem, Sarah Hensley, and Ben Knowles, and published by the UF Department of 4-H Youth Development, July 2014.